الحديث وعلومه في المدارس الأهلية بولاية قدح بماليزيا : (دراسة تقويمية لمدارس ثلاث) - Mohd Arif Nazri
This study "The hadith and its Sciences in Private Islamic Schools in the State of Kedah, Malaysia: An Evaluation of Three Schools" addresses a unique type of private Islamic school that specializes in the teaching of Islamic sciences. It showcases the efforts of Malay scholars in the field of education, especially the development of Islamic curriculum, and the suitability between the theoretical and practical aspects. This study also evaluates the syllabus of the three schools in the field of hadith and its science and concludes with some comments and recommendations. The methodology followed in this study is the survey method research consisting of data collection from schools, data analysis and a comparative study. It found that the focus on the study of hadith in Malaysia whether in the traditional system or modem system is only minimal. Even though private schools have succeeded in producing commendable Islamic personalities that integrated the aspects of knowledge, practice and values; the sidelining of some aspects has resulted in some weaknesses. But the difficulties and problems faced by these schools are temporary in nature and can be overcome with the contribution of lecturers, learners, intellectual institutions, the government and the public.